Demand and Supply: Digital Competencies in Humanities (Training and Practice : Journal of Educational Sciences, 2021)
The study summarises the opportunities and possibilities of ICT and digital humanities in the field of humanities. Based on the author’s experience the study introduces several ways of enhancing digital competences in teacher training and Hungarian linguistics. After a short demonstration of the so-called digital competences, it outlines the requirements and infocommunication techniques of text-based information extraction. The focus placed by the author lies on the digital competences of students, on their set of knowledge in using data based infocommunication techniques, laying down basic strategies for their measurement and evaluation.